Melatonin: A master regulator of plant development and stress responses. Issue 1 (22nd August 2020) - Sun, Chengliang; Liu, Lijuan; Wang, Luxuan; Li, Baohai; Jin, Chongwei; Lin, Xianyong
Abstract: Melatonin is a pleiotropic molecule with multiple functions in plants. Since the discovery of melatonin in plants, numerous studies have provided insight into the biosynthesis, catabolism, and physiological and biochemical functions of this important molecule. Here, we describe the biosynthesis of melatonin from tryptophan, as well as its various degradation pathways in plants. The identification of a putative melatonin receptor in plants has led to the hypothesis that melatonin is a hormone involved in regulating plant growth, aerial organ development, root morphology, and the floral transition. The universal antioxidant activity of melatonin and its role in preserving chlorophyll might explain its anti‐senescence capacity in aging leaves. An impressive amount of research has focused on the role of melatonin in modulating postharvest fruit ripening by regulating the expression of ethylene‐related genes. Recent evidence also indicated that melatonin functions in the plant's response to biotic stress, cooperating with other phytohormones and well‐known molecules such as reactive oxygen species and nitric oxide. Finally, great progress has been made towards understanding how melatonin alleviates the effects of various abiotic stresses, including salt, drought, extreme temperature, and heavy metal stress. Given its diverse roles, we propose that melatonin is a master regulator in plants. Abstract : Phytomelatonin is emerging as a master regulator of plant development and stress responses, exerting its effects by regulating various elements related to the redox network or interfering with the activities of other phytohormones.